Reciprocal Mentoring: Can it help prevent attrition for beginning teachers? - Paris, Lisa (Edith Cowan University, 2013)
Forty per cent of new teachers in Australia leave the profession in the first five years. Stress, induction failure and professional isolation have been identified as key attrition factors. Mentoring has been used both internationally and in Australia to enhance induction and reduce profession isolation; however, these mentoring relationships are often fragile and there is a need to establish more effective mentoring models. Reciprocal Mentoring (RM) pairs two equal, though differently skilled, experts who act in the role of mentor and mentee to each other for their mutual benefit. The RM approach is designed to support beginning teachers as they transition to the profession and to facilitate improved retention. The 'Better Transitions to Teaching' inquiry was initiated by Edith Cowan University in 2011. It investigated the impact of RM on the first year experience of 11 (visual arts) Western Australian beginning teachers, following their participation in an RM residency in 2010. A major outcome of the research was that at the end of the first year all beginning teacher participants were still working in the profession. All reported experiencing personal/professional challenges during their first year and, importantly, the support of mentors appeared to make a significant and positive difference to the participants' transition experience and their first year of teaching.